Simulation model of power generation and the shadow effect of foldable solar panels used in agrivoltaics system - Lama, Ramesh Kumar; Jeong, Heon (Frontiers in Energy Research, 2024)
This paper presents a comprehensive analysis of foldable solar panels used in Agrivoltaics Systems (AVS), focusing on the dual benefits of optimized land use for agriculture and solar power generation. Employing simulation techniques, the study investigates the impact of inter-panel shadow effects on energy capture in systems using multiple foldable solar panels. Key findings indicate that foldable panels achieve optimal performance during periods with shorter daylight hours, demonstrating high seasonal variability in power generation. The study shows that foldable panels, which can adjust their angle relative to the sun's position, are particularly effective at reducing the loss of solar irradiance due to shading, compared to fixed panels. Additionally, this study highlights the potential of foldable solar panel systems in AVS to adapt to varying solar conditions, thereby enhancing land use optimization for sustainable agricultural and power generation practices.